2005
DOI: 10.1097/00129492-200501000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control after Cochlear Implant Surgery by Means of Rotational Tomography

Abstract: The impact of these findings may influence further developments of electrode arrays as well as surgical techniques for implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
1
13

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(132 citation statements)
references
References 8 publications
4
114
1
13
Order By: Relevance
“…75,81 A recent study has also explored the utility of CBCT in evaluating progressive hearing loss. Dalchow et al 82 submitted 25 patients with audiometry-confirmed conductive hearing loss to preoperative CBCT and concluded that CBCT could be accurate both in predicting the continuity of the ossicular chain and in detecting ossicular erosions.…”
Section: Sinus Imaging/frontal Recessmentioning
confidence: 99%
“…75,81 A recent study has also explored the utility of CBCT in evaluating progressive hearing loss. Dalchow et al 82 submitted 25 patients with audiometry-confirmed conductive hearing loss to preoperative CBCT and concluded that CBCT could be accurate both in predicting the continuity of the ossicular chain and in detecting ossicular erosions.…”
Section: Sinus Imaging/frontal Recessmentioning
confidence: 99%
“…For this reason we feel that it will be necessary for manufacturers to approach the development of future electrodes with a very broad view that includes a critical examination of current electrodes, anatomy of the ST, the surgical approach, surgical instrumentation and device specific training for surgeons. We envision that advances in imaging will allow both improved speech processor fitting by documenting the unique position of each electrode within the cochlea and increased safety by giving the surgeon detailed feedback after each surgery [158][159][160]. With the application of successful design features from current electrodes and improved surgical training and instrumentation, it appears that relatively modest modifications of the current designs will ensure routine atraumatic electrode insertion to a depth of up to 400°.…”
Section: Future Intracochlear Electrode Arraysmentioning
confidence: 99%
“…[16,17] Aschendorff ve ark. [18] elektrot yerleşim derinliğinin, Eisenberg ve ark. [17] ise tek kanallı implantın ameliyat sonrası denge ve vestibüler semptomlar üzerine olası bir etkisinin olmadığını belirtmişlerdir.…”
Section: Discussionunclassified